Influence of arrangement and configuration of extraction wells to the capture zone in pump and treat system - Farzana Izzati Che Daud,; Yusyalia Abdul Halim,; Kuan, Woei Keong (Penerbit Universiti Kebangsaan Malaysia, 2024)
Urbanization, industrial wastes, non-point sources from agricultural activities, and various types of wastes within a landfill system have posed major threats to groundwater quality in Malaysia. One of the common contaminated groundwater remediation techniques is pump and treat system. This work was conducted to investigate the influence of extraction wells in pump and treat system to remove the contaminant by evaluating the capture zone under different arrangements and configurations of well in an unconfined aquifer system. A conceptual model was developed using PMWIN software at pre-determined soil characteristics and boundary conditions. In the numerical simulation, 17 models were simulated to examine the influence of pumping rate of wells, distance between two wells, wells orientation and the number of wells to the width of capture zone under four study cases. The results show that the width of the capture zone corresponded linearly to the increment of pumping rate. In the two and four wells system, the width of the capture zone was reduced when the extraction wells were aligned parallelly to the flow direction and the distance between wells were increased. However, the capture zone was extended when the well orientation was aligned perpendicular to the flow direction. The simulation results show that the drawdown in the wells was reduced when the number of wells has increased due to the distribution of total pumping rate into two or four wells system. The finding indicated that the arrangement of extraction wells in pump and treat system has a major impact on the capture zone induced by the wells. The simulation results can help to improve the effectiveness of extraction well in pump and treat system by optimizing the extraction process and thus minimize the cost of groundwater remediation.